Repair, brokenness, breakthrough : ethnographic responses - Martínez, Francisco, 1982-; Laviolette, Patrick (Politics of repair, 2019)
"What does it mean to claim that something is broken? What is the connection between tinkering and innovation? And how much tolerance for failure do our societies have? Exploring some of the ways in which repair practices and perceptions of brokenness vary culturally, Repair, Brokenness, Breakthrough argues that repair is an attempt to extend the life of things as well as an answer to failures, gaps, wrongdoings and leftovers. The set of contributions illustrates the strong affective power hidden in situations of disrepair and repair; broken objects often bring strong emotions into play, but also energising reactions of creative action"--